THE EFFECT OF GREEN QUALITY MANAGEMENT ON GREEN MANUFACTURING - Abdul Mohsen Abdel Sarhan; Dr. Kabas Zuhair Abdul Karim; M. Hafsa Atallah (Scholars Digest Publishing, 2024)
The research seeks to identify the nature of the relationship between the two variables of the study: green quality management, represented by six dimensions (green quality performance, green quality reliability, green quality suitability, green quality durability, green quality conformity, and sustainability) and green manufacturing, represented by (the environmental management system, green purchasing, social and environmental responsibility, and energy-saving technologies in the company). Central refineries. The problem of the study stemmed from the presence of challenges facing organizations towards paying attention to the environmental aspect and the lack of awareness of it. This is what appears from the decline in the level of application of green manufacturing as a result of weak green quality management. To reach the research objectives and answer the questions raised, the research was applied to a sample of (117) officials from the general manager, department heads and their assistants, and officials of divisions and units at all levels of the company. The study relied on the descriptive analytical approach according to a questionnaire prepared for this purpose and distributed to officials at all administrative levels in the company. To reach the results, the statistical program (SPSS) was used (and the study concluded with a set of results, the most important of which is the existence of a positive, statistically significant correlation between green quality management and green manufacturing. In light of that relationship, the researcher presented a set of recommendations, the most prominent of which was the necessity of adopting the concept of green quality management and the green manufacturing system, as a means that works to reduce costs and reduce emissions and resulting carbons. Of the manufacturing operations in the researched company.
Keywords: Green quality management, green manufacturing, sustainability, environmental management system, social and environmental responsibility.